Implikasi Hukum Penerapan Asas Keseimbangan Pihak-Pihak Dalam Persidangan Perkara Perdata - Dwi Handayani, Dwi Handayani (UNES Law Review, 2024)
The phenomenon of the birth of civil case decisions that do not reflect the fairness and balance of litigants will injure justice and legal certainty. The legal principle of hearing parties is a manifestation of the principle of balance in the litigation process in court, but in practice this is often violated because there has been no strict sanction for violations of legal principles in judges' decisions, and is only subject to violations of the code of ethics. This has legal implications for the final decision, whether it provides justice and balance for the litigants. Similarly, the real truth of a formal nature will be sought in the trial of civil cases in a fair and balanced manner. Using qualitative approach methods with primary and secondary data sources which will then be analyzed in an analytical descriptive way to answer legal issues and research objectives. The results showed that the application of the principle of balance of parties in the trial of civil cases that are fair and balanced, does not cause problems if applied by judges in accordance with the process in the HIR / RBG legislation. But if it is the other way around, it will have implications for a final verdict that does not reflect the fairness, balance of the parties and the sense of justice of the community.